Body composition changes during fasting among female youngsters / Wan Mohd Norsyam ...[et al.] - Mohd Norsyam, Wan; Mat Aziz, Norazmira; Azam, Zulkhairi; Sariman, Hanifa (Academy of Contemporary Islamic Studies (ACIS), 2016)
The effects of fasting on body compositions are still inconclusive. Therefore the aim of the study is to determine the changes in body compositions particularly among female youngsters throughout fasting during the whole Ramadhan. Body weight, height, waist and hip circumference were measured and body mass index (BMI) and waist to hip ratio (WHR) were calculated while body fat percentage was determined using bioelectrical impedance analyzer. 67 female youngsters who strictly commit fasting, aged between 18 to 21 years old were recruited in this study. The study was carried out for six weeks, which started a week before Ramadan until a week after Ramadan ended. Results showed a significant decreased (P < 0.001) in body weight, BMI and body fat percentage after the third week of fasting as compared to initial measurement before Ramadhan. However, a significant increase (P < 0.001) in body weight, BMI, and body fat percentage was found a week after Ramadhan compared to the third week of Ramadhan. No significance difference observed on WHR throughout Ramadhan. Therefore Ramadhan fasting lead to body weight, BMI and body fat reduction among female youngsters which may enhance general human health.